Development and characterization of biodegradable blends of low density polyethylene (LDPE) incorperated with thermoplastic sago starch - Shaharuddin , Kormin (2012)
Starch-based polymeric materials offer a renewable, economical alternative to existing petroleum based, non-renewable or costly polymeric materials.The aim of this study is to develop degradable starch-low density polyethylene(LDPE)blend with enhanced mechanical properties.This research studies the effect of different filler loading,effect of compatibilizer and different kind of plasticizer.The compounding of the LDPE with sago starch was prepared via a twin screw extruder followed by injection molding.Studies on their physical,mechanical properties and thermal properties of each formulation were carried out by density, melt flow index (MFI),tensile,flexural,impact, thermogravimetry analyzer(TGA-DTA)and differential scanning calorimetry(DSC).The presence of high starch contents had an adverse effect on the mechanical properties of LDPE/starch blends.However,the addition of compatibilizer or plasticizer improved the interfacial adhesion between the two materials, hence,improved the tensile properties of the blends. Meanwhile,study of degradation of sago starch filled-LDPE (LDPE/SS)blend was carried by hydrolysis,fungi exposure, natural weathering and soil burial exposure analysis.The biodegradability of sago starch–filled LDPE blend was studied by monitoring its weight loss.Incorporating sago starch with LDPE improved the weight loss.Tensile tests, TGA and SEM imaging were also carried out on the samples before and after degradation.Imaging showed that the increase in starch content from 5% to 20% in the formulations increases the biodegradability of the samples.The scanning electron micrographs(SEM)support the findings of biodegradation properties of LDPE/SS blend, compatibilized LDPE/SS and plasticized LDPE/SS blend.In order to increase the compatibility between LDPE and starch,malaeic anhydride was used to graft onto the LDPE molecules(compatibilized LDPE/SS).After using the proper composition and processing condition,mechanical properties of compatibilized LDPE/SS blend were found significantly higher than those of the LDPE/SS blend with the same starch contents. The second part of the study investigated the effects of different types of plasticizer(sucrose,urea,glycerol and sorbitol)and its content on the structure and properties of the LDPE/SS blend.Mechanical properties of plasticized LDPE/SS were found higher than unplasticized LDPE/SS blend.